The necropolises of “Cherna–Sihleanu” type: are they biritual and what in fact does biritualism mean? - Vladimir Staykov (Българско е-Списание за Археология)
The paper reviews a group of five Early Medieval necropolises on the territories of modern-day Northeast Bulgaria and Southeast Romania, which demonstrate some intriguing features. Although the predominant burial rite is cremation, in some rare cases, when the deceased is a child, the remains are only inhumated, without incineration. A definition of site-type is attempted based on the evidence from the “Cherna–Sihleanu” necropolises and the five sites are distinguished from other synchronous biritual cemeteries in the area. The analysis of the burial ritual in those sites, as well as other biritual cemeteries poses the questions what does biritualism mean in general, when should a certain necropolis be defined as biritual and what kinds of biritualism are to be observed in the archaeological record. Some assumptions are made about the factors and conditions leading to the situation we see in the “Cherna–Sihleanu” group and examples are given of analogous sites, where an “atypical” biritualism is documented.